Placental Growth Factor Predicts Time to Delivery in Women With Signs or Symptoms of Early Preterm Preeclampsia: A Prospective Multicenter Study. Issue 4 (December 2020) - Barton, J.R.; Woelkers, D.A.; Newman, R.B.; Combs, C.A.; How, H.Y.; Boggess, K.A.; Martin, J.N.; Kupfer, K.; Sibai, B.M.
Abstract : ( Am J Obstet Gynecol . 2020;222:259.e1–259.e11) There is a clear need for quantitative testing methods to determine which patients with signs of preeclampsia may be at heightened risk for adverse pregnancy outcomes. The altered angiogenic factor concentrations including placental growth factor (PlGF) have been found to be associated with preeclampsia and precede the onset of preeclampsia by several weeks. While previous studies have found encouraging evidence that PlGF concentrations may predict adverse pregnancy outcomes, the association between angiogenic factors and time to delivery (TTD) is still unclear. This study aimed to examine the relationship between TTD and PlGF in pregnant women with gestational age <35 weeks with signs of preeclampsia and to evaluate the performance of PlGF as a predictor for TTD.